Integrating Nursing and Family Medicine: A Comprehensive Review of Interdisciplinary Approaches in Patient-Centered Care - Alshehri, Haya Muhaysin; Alharbi , Majed Hulayyil; Juharji, Hanaa Mohammedzakary; Albishry , Mohammed Ahmad; Omairan , Aisha Mohib; Albeshri, Yousef Mansoor Ahmed; Albarkatee, Eman saleem; Almuwallad , Abeer Abduraboh; kassem, Etaf ali; Alharthi , Amirah hasan; Alqurashi, Hamed Obaid safar (Journal of Ecohumanism, 2024)
This review explores the integration of nursing and family medicine in promoting patient-centered care through interdisciplinary approaches. Family medicine and nursing play complementary roles in primary healthcare, with nurses increasingly involved in collaborative efforts to address complex patient needs. This article examines current models of interdisciplinary collaboration, including team-based care and the Patient-Centered Medical Home (PCMH), and their impact on patient outcomes, cost-efficiency, and holistic care delivery. Additionally, the review highlights barriers to integration, such as role ambiguity, communication challenges, and institutional constraints, and offers strategies for overcoming these obstacles, including interdisciplinary training, supportive policies, and integrated health IT systems. Case studies of successful integration are presented, underscoring the practical benefits of collaborative care. The review concludes with implications for practice, suggesting that integrating nursing into family medicine enhances patient-centered care, especially in managing chronic conditions and preventive care. Further research is encouraged to establish best practices and policies that support effective interdisciplinary collaboration in primary care